An overview of the nutrition knowledge systems and networks in India - Anuradha, T.; Kunaratnam, Yaso; McGrath, Louise (International Food Policy Research Institute, 2013)
One of the objectives of POSHAN is to facilitate the availability of, access to, and use of knowledge to inform program and policy decisions among stakeholders working in nutrition in India. To understand how POSHAN can best support and strengthen knowledge mobilization in nutrition, a team from POSHAN reviewed the reach, use, and role of existing knowledge systems and knowledge networks (Exhibit 1) in India.